2019
DOI: 10.1159/000496691
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining of Increased Expression of Enhancer of Zeste Homolog 2 (EZH2) in Diffuse Midline Glioma H3K27M-Mutant Patients with Poor Survival

Abstract: <b><i>Introduction:</i></b> The interaction of K27M mutation in histone H3 (H3K27M mutation) with polycomb repressive complex 2 (PRC2) is facilitated by the enhancer of zeste homolog 2 (EZH2). Subsequently, this interaction leads to the global reduction level of H3K27me3. We analyzed the EZH2 expression level in H3K27M mutation-positive tumors and revealed the association of high EZH2 expression with poor survival. <b><i>Methods:</i></b> Our study included 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…In addition, other immunohistochemistry staining results in our cases also gave more perspective. The ATRX and p53 immunostaining positive cutoff values were both 10% nuclear staining as described previously [16]. All of our cases showed consistent results with previous reports of ATRX-negative immunostaining expressions [11,17].…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…In addition, other immunohistochemistry staining results in our cases also gave more perspective. The ATRX and p53 immunostaining positive cutoff values were both 10% nuclear staining as described previously [16]. All of our cases showed consistent results with previous reports of ATRX-negative immunostaining expressions [11,17].…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…EZH2 is expression is low in the normal liver, and is associated with methylation of histone H3K27 and recruitment of methyltransferases, which are involved in DNA replication for cancer progression, and stem cell maintenance and differentiation of other cell lineages, such as immune cells (32,33). Several studies have confirmed its prognostic value and importance in various types of cancer, including lymphoma, glioma, head and neck carcinoma, and cervical neoplasia (34)(35)(36)(37)(38). Novel therapeutic methods have been developed to target EZH2, although high expression of EZH2 is not always correlated with the malignancy of a cancer, such as in colorectal cancer (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed eight articles and 187 cases (including the 23 cases in this study) of adult diffuse midline glioma. 13,[18][19][20][21][22][23][24] The prognosis was examined by the presence or absence of K27M or by histological grade in 171 or 164 cases, respectively. When the prognosis was examined based on the presence or absence of K27M mutation, cases that did not determine K27M mutation status were excluded and we reviewed 171 cases.…”
Section: Review Of Literature: H3k27m-mutant and Histological Gradementioning
confidence: 99%